Ten benefits of using instructor-developed screencasts to help students learn maths: an AIT case study - Tunku Ahmad, Tunku Badariah; Doheny, Frank; Faherty, Sheila; Harding, Nuala (2013)
In January 2013, we undertook a case study to look at how first, second and third year AIT students taking Algebra and Calculus courses under Mr Frank Doheny (N=266) used screencasts to help them learn Maths. The screencasts, ranging between 1:49 and 11:20 minutes in length, were developed to demonstrate specific Maths keyskills that students had difficulty with. To explore students’ views and uses of the screencasts, we administered an open-response survey on the relevant Maths Moodle pages. A total of 138 students from Mechanical & Renewable Engineering(MRE), Computer Network Management (CNM), Electronic & Computer Engineering (ECE), and Sports & Nutrition Science (SNS) responded to the survey, constituting a response rate of 52%. Using an inductive Thematic Content Analysis (TCA), we generated ten themes from their responses that represented ten benefits of using the screencasts. These are what students had to say about their screencast use and how the videos had aided their Maths learning.